Efficacy of preemptive endoscopic submucosal dissection and surgery for synchronous colorectal neoplasms. (2nd August 2020) - Yabuuchi, Yohei; Imai, Kenichiro; Hotta, Kinichi; Ito, Sayo; Kishida, Yoshihiro; Manabe, Shoichi; Yamaoka, Yusuke; Hino, Hitoshi; Kagawa, Hiroyasu; Shiomi, Akio; Ono, Hiroyuki
Abstract: Background and aim: If patients with surgically resectable colorectal cancershave synchronous colorectal neoplasms that are difficult to remove by endoscopic mucosal resection, preemptive endoscopic submucosal dissection (ESD) can avoid excessive colorectal resection. The aim of this study was to evaluate the efficacy of the strategy of preemptive ESD and surgery for synchronous colorectal neoplasms. Methods: Patients who underwent preemptive ESD and surgery for synchronous colorectal neoplasms between September 2002 and December 2017 were enrolled in this retrospective cohort study. The proportion of cases in which extended surgery could be avoided following curative ESD was calculated. Clinicopathological characteristics were evaluated for all patients and long-term outcomes were analyzed for patients who underwent curative ESD and surgery. Results: A total of 45 consecutive patients with 47 endoscopically-resected lesions and 46 surgically-resected lesions were retrospectively evaluated. Curative ESD was achieved in 44 lesions (93.6%) and an extended surgical procedure could be avoided in 42 patients (93.3%). Intraoperative perforation occurred in two lesions (4.3%), delayed perforation in one lesion (2.1%), and delayed bleeding in two lesions (4.3%). Final stages were as follows: stage 0, 3 patients (7.1%); stage I, 23 patients (54.8%); stage II, 3 patients (7.1%); stage III, 12 patients (28.6%); and stage IV, 1 patient (2.4%). The 5-year overall survival rates of patients with all pathological stages, stage 0–II, and stage III–IV were 93.7%, 100%, and 79.1%, respectively. Conclusion: The strategy of preemptive ESD and surgery for synchronous colorectal neoplasms is minimally invasive and has a favorable prognosis.